An insight into hybrid agile software development approach and software security among software engineers: a critical evaluation - Maidin, Siti Sarah; Yahya, Norzariyah (Little Lion Scientific, 2024)
The aim of this paper is to provide an overview of the hybrid agile development approach specifically in software development. Different platforms were used to investigate the factors that influence developers in choosing the preferred model for software development. In addition, this paper also examines the security elements in a software development project. It identified 3 factors that motivate software developers to focus on software security in a project. These are the company's policies and culture, i.e., the overall company culture regarding security, the application domain, i.e., the developers' perception of the benefits of security for their applications, and finally, the use and complexity of security tools. This article is organized as follows. The first section is the introduction, which explains the software development methodology. The subsequent Materials and Methods section provides an overview of searching journals in various databases, including Google Scholar, IEEE, ACM, and Science Direct. This paper concludes with recommendations on other areas that can be explored in the area of software security in the context of the hybrid agile approach.